Navigating Morocco’s Public Higher Education Landscape: Characteristics, Endeavors & Setbacks. - JAIDA Fatima Ezzahra; HAOUCHA Malika (African Scientific Journal, 2025)
Abstract: Since Morocco’s independence in 1956, Morocco’s higher education system has reached new heights, embarking on a series of changes and reforms aimed at modernizing and improving its quality and performance. However, despite notable investments and efforts to elevate the system, its persistent shortcomings have long perplexed Moroccan policymakers, as it continues to face numerous challenges that prevent the effective implementation of undertaken reforms and holding back their sustained progress. Our article adopts a theoretical approach through a review of the existing literature. It provides an in-depth exploration of the Moroccan higher education landscape, with a strong emphasis on Moroccan public universities, by examining the key factors shaping the system, its unique characteristics and endeavors, while unpacking the main challenges weighing on the achievement of its full potential and desired outcomes. In pursuit of elevating the Moroccan higher education sector, our article concludes that a steadfast commitment to world-class education standards is essential to enhancing its performance, visibility, and competitiveness on the global stage. This involves reinforcing English as a medium of instruction, overhauling academic catalogs, improving the quality of teaching and research output, and expanding international partnerships and collaborations, all while emancipating from colonial legacies and adopting a 'glocal' approach, balancing Western, non-Western, and Moroccan perspectives to better suit the country's unique needs and characteristics, ensuring a modern, inclusive, and sustainable public higher education system in Morocco. Keywords: Morocco’s Higher Education, Moroccan Public Universities, Governance, Funding, Access and Admission, Quality in Teaching and Scientific Research, Internationalization, Ranking, Language Dynamics, Student Mobility, Challenges.